Routinization of HIV Testing in an Inpatient Setting: A Systematic Process for Organizational Change. Issue 3 (May 2016) - Mignano, Jamie L.; Miner, Lucy; Cafeo, Christina; Spencer, Derek E.; Gulati, Mangla; Brown, Travis; Borkoski, Ruth; Gibson-Magri, Kate; Canzoniero, Jenna; Gottlieb, Jonathan E.; Rowen, Lisa
Abstract : Abstract: In 2006, the U.S. Centers for Disease Control and Prevention released revised recommendations for routinization of HIV testing in healthcare settings. Health professionals have been challenged to incorporate these guidelines. In March 2013, a routine HIV testing initiative was launched at a large urban academic medical center in a high prevalence region. The goal was to routinize HIV testing by achieving a 75% offer and 75% acceptance rate and promoting linkage to care in the inpatient setting. A systematic six-step organizational change process included stakeholder buy-in, identification of an interdisciplinary leadership team, infrastructure development, staff education, implementation, and continuous quality improvement. Success was measured by monitoring the percentage of offered and accepted HIV tests from March to December 2013. The targeted offer rate was exceeded consistently once nurses became part of the consent process (September 2013). Fifteen persons were newly diagnosed with HIV. Seventy-eight persons were identified as previously diagnosed with HIV, but not engaged in care. Through this process, patients who may have remained undiagnosed or out-of-care were identified and linked to care. The authors propose that this process can be replicated in other settings. Increasing identification and treatment will improve the individual patient's health and reduce community disease burden. Abstract : Supplemental Digital Content is Available in the Text.